SHOPPING LIST APPLICATION PROGRAM WITH TURBO PASCAL 7.0 - Ruli Rahmadi; IRE Puspa Wardani, SKom, MMSI (Jurnal Sistem Informasi, 2000)
The application program is a program created for a particular data processing system.Flowchart is a chart that describes in detail the steps of the process of the program.Computer programming language Turbo Pascal is a high-level language whoseorientation in all fields. Pascal has control structures, namely the ability to dorepetition pascal language, choosing an action or branching in an action.There are several ways you can do to reduce the number of inputs that will beinserted into a computer without compromising completeness. These ways is the firstby using the code. Use the code will make inputs into shorter and unique. Both arerelatively constant data stored in the master file reference. Third time and date and thefourth was taken from the computer calculations performed by a computer routine.